RISK FACTORS AND NOSOCOMIAL INFECTIONS CAUSED BY ENTEROCOCCI - N. I. Gabrielyan; E. M. Gorskaya; O. M. Tsiroulnikova (Вестник трансплантологии и искусственных органов)
Aim: to analyze nosocomial infections and risk factors caused by enterococci. Review of the foreign and domestic literature on biology and virulence factors of enterococci being the leading causative agents of nosocomial infections is done. Information on risk factors and postoperative infectious complications, pathogens of which are enterococci, in surgical hospitals and hospitals for organ transplantations is provided. The growth of antibiotic resistance in enterococci and the relationship between mortality rate and prevalence rate of antibiotic resistant strains are emphasized